Bahasa inggris - Fairus Zabadi (Journal Innovation of Civil Engineering (JICE), 2023)
Utilization of water resources and management is an important factor and has a decisive role in order to increase production per plant in general and crop production in particular. In order to maintain self-sufficiency in food, it is necessary to make efforts to continuously increase the intensity of potential food crops. These efforts include optimizing the proper distribution of water utilization. Factors to determine the need for irrigation water include land preparation, consumptive use, percolation and seepage, replacement of water layers, and effective rainfall. While the method used in this study is optimization using a linear program using the Solver facility in Microsoft Excel with the aim of optimizing the availability of irrigation water so as to produce maximum profits and distribution of irrigation utilization that is more effective and efficient. From the optimization results using the Solver and Microsoft Excel tools, it can be seen that the maximum area of ​​land that can be planted with the available inflow at the intake for MTI (Rice I 2086 Ha/Tobacco II 667.54 Ha), MT-II (Rice I 667, 54 Ha/Tobacco I 1391 Ha/PolowijoI 567.35 Ha/Rice II 128.11 Ha), MT III (Polowijo I 323.65 Ha/Rice II 348.89 Ha/Tobacco II 1261.46 Ha/Polowijo II 825, 00) and provides an analysis of the maximum profit of agricultural products of Rp. 178,183,800,000.00,-.   Keywords: Linear Program Optimization; Utilization of Water Resources; Agricultural Benefits; Klampis Irrigation.